Efficacy of a Lifestyle Program Designed to Help Indigent, Obese Adult Patients Lose Weight - Duggins, Maurice L.; Lewis, Douglas P.; Harvey, Anne T. (Kansas Journal of Medicine, 2019)
Introduction. Modest weight loss (5 to 7%) reduced the incidenceof type II diabetes in the Diabetes Prevention Program (DDP) trial.A DPP-inspired lifestyle intervention requiring minimal patientself-data collection and tailored to low-SES patients throughminimal cost was developed for our indigent, obese patients.Methods. Obese (BMI ≥ 30 kg/m2), indigent (≤ 200% FederalPoverty Level) adults (age 18 - 70) were offered a nocostweight loss intervention as an adjunct to their usual primarycare in a residency outpatient clinic. The interventionprovided options for diet plans and social support. The goalwas to achieve a 5% loss of body weight over six months.Results. The sample (n = 158) was 86% female and 62% white,with a median age of 45 and median BMI of 40.9. Two-thirds ofsubjects chose the 50% diet; YMCA membership was selected byall but one. The 5% weight loss goal was met by 12.8%; another8.7% gained that amount. Subjects who either had pre-existingYMCA membership or used their provided membership weresuccessful, relative to those who received but never used theirmembership (0.6% loss vs 0.9% gain; p < 0.05). Changes in weightover six months were observed in the youngest (gain of 3.9 lbs.,p < 0.05) and the oldest (loss of 4.0 lbs., p < 0.05) age quartiles.Conclusions. A DPP-inspired lifestyle intervention tailoredto low-SES patients did not lead to overall weight loss, reinforcingthat weight reduction programs must provide a significantamount of support for participants to see success.Older age and a behavioral commitment to physical activityimproved the likelihood of success. KS J Med 2016;9(4):83-87.